Communication Strategy Used By English Department Students Of Muhammadiyah University Of Surakarta: A Case Study In Saturday English Gathering (SEGA) Program - Rolitasari, Aisyah; , Prof. Dr. Endang Fauziati, M.Hum; , Mauly Halwat Hikmat, Ph.D (2015)
This research aims to describe the communication strategies used by students of Saturday English Gathering of Muhammadiyah University of Surakarta. The study is also to the reference for the better of teaching speaking. The data of this research containing communication strategies used by students of Saturday English Gathering Muhammadiyah University of Surakarta in 2014/2015 academic year during they are speaking. The writer takes 3 groups of SEGA program, with the total 30 students as the subject of the research. There are 161 percent of each types of communication strategies. The writer uses descriptive qualitative method in analyzing the data. The data is based on Celce-Murcia taxonomy of communication strategies. The result of this study shows that there are five types of communication strategies, the most dominant types of communication strategies used by students in SEGA program is fillers with 37,26%, and the type of communication strategies rarely used by the students is non-linguistic means and restructuring with 0,62%. The result above implies that teaching communication strategies is needed for the students who still have limited knowledge in the target language. By teaching communication strategies, the students will be more aware of when they can use communication strategies for speaking better.